Dopamine Dysregulation and Altered Responses to Drugs Affecting Dopaminergic Transmission in a New Dopamine Transporter Knockout (DAT-KO) Rat Model. (21st May 2022) - Lloyd, Jordan T.; Yee, Andrew G.; Kalligappa, Prasanna K.; Jabed, Anower; Cheung, Pang Y.; Todd, Kathryn L.; Karunasinghe, Rashika N.; Vlajkovic, Srdjan M.; Freestone, Peter S.; Lipski, Janusz
Highlights: Our genetic model extends the range of animals for dopamine dysregulation studies. Voltammetry was used to measure dopamine both in the striatum and substantia nigra. Genetic DAT inactivation enhances electrically-stimulated dopamine overflow. MAO greatly contributes to dopamine clearance after L-DOPA-induced release. OCT3 contributes to DA clearance in dorsal striatum after genetic DAT inactivation. Abstract: Under normal conditions, dopamine (DA) clearance after release largely depends on uptake by the DA transporter (DAT). DAT expression/activity is reduced in some neuropsychiatric and neurological disorders. Our aim was to characterize the behavioral, neurochemical and electrophysiological effects of eliminating DAT in a novel knockout rat model we generated using CRISPR/Cas9. Consistent with existing DAT-KO models, our DAT-KO rats displayed increased locomotion, paradoxical calming by amphetamine, and reduced kinetics of DA clearance after stimulated release. Reduced DA kinetics were demonstrated using fast-scan cyclic voltammetry in brain slices containing the striatum or substantia nigra pars compacta (SNc) and in the dorsal striatum in vivo . Cocaine enhanced DA release in wild-type (WT) but not DAT-KO rats. Basal extracellular DA concentration measured with fast-scan controlled-adsorption voltammetry was higher in DAT-KO rats both in the striatum and SNc and was enhanced by L-DOPA (particularly after pharmacological block of monoamine oxidase), confirming that DA release after L-DOPA is not due to DAT reversal. The baseline firing frequency of SNc neurons was similar in both genotypes. However, D2 receptor-mediated inhibition of firing (by quinpirole or L-DOPA) was blunted in DAT-KO rats, while GABAB -mediated inhibition was preserved. We have also provided new data for the DAT-KO rat regarding the effects of slowing DA diffusion with dextran and blocking organic cation transporter 3 with corticosterone. Together, our results validate our DAT-KO rat and provide new insights into the mechanisms of chronic dysregulation of the DA system by addressing several unresolved issues in previous studies with other DAT-KO models.